2021
DOI: 10.1097/aog.0000000000004382
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Cervical Ripening

Abstract: E, et al. Outpatient cervical ripening: a systematic review and meta-analysis. Obstet Gynecol 2021;137. The authors provided this information as a supplement to their article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…The authors concluded that there are currently limited data available to compare the efficacy and safety of outpatient versus inpatient induction, making it difficult to draw any definite conclusions 47 . The latest review and meta‐analysis published in March 2021 including 30 RCTs and 10 cohort studies, including 9618 women, came to the same result: no increase in cesarean section rate in a low‐risk population in a high‐income setting, but low or insufficient evidence for the safety aspect 49 . A previous Cochrane review evaluating the effects of outpatient induction on maternal and fetal/neonatal outcomes, including 1439 women, came to the same conclusion 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that there are currently limited data available to compare the efficacy and safety of outpatient versus inpatient induction, making it difficult to draw any definite conclusions 47 . The latest review and meta‐analysis published in March 2021 including 30 RCTs and 10 cohort studies, including 9618 women, came to the same result: no increase in cesarean section rate in a low‐risk population in a high‐income setting, but low or insufficient evidence for the safety aspect 49 . A previous Cochrane review evaluating the effects of outpatient induction on maternal and fetal/neonatal outcomes, including 1439 women, came to the same conclusion 8 .…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing number of labor inductions, interest in performing cervical ripening and IOL in an outpatient setting has increased 1,2,8,9 . IOL, especially for primiparas with an unfavorable cervix, can take a substantial amount of time, ranging from hours to days.…”
Section: Introductionmentioning
confidence: 99%
“…Undergoing cervical ripening at home is an attractive option to reduce potentially the duration of antenatal hospital stay, reduce strain on healthcare resources, increase satisfaction and comfort for patients, and to reduce financial costs 8,10–15 . Currently, there is limited evidence for IOL with oral misoprostol in an outpatient setting 2,6,9,14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations